Korringa-Kohn-Rostoker Green-function formalism for ballistic transport - P. Mavropoulos; N. Papanikolaou; P.H. Dederichs (PHYSICAL REVIEW B, 2004)
We develop a method for the calculation of ballistic transport from first principles. The multiple scattering screened Korringa-Kohn-Rostoker (KKR) method is combined with a Green-function formulation of the Landauer approach for the ballistic transport. We obtain an efficient O(N) algorithm for the calculation of ballistic conductance through a scattering region connected to semi-infinite crystalline leads. In particular we generalize the results of Baranger and Stone in the case of Bloch wave boundary conditions and, we discuss relevant properties of the S matrix. We consider the implications on the application of the formalism in conjunction with a cellular multiple scattering description of the electronic structure; and demonstrate the convergence properties concerning the angular momentum expansions.